Molecular Detection of Carbapenemase-Encoding Genes in Multidrug-Resistant Acinetobacter baumannii Clinical Isolates in South Africa - Anane, Yaw Adjei (Int J Microbiol, 2020)
INTRODUCTION: Carbapenem-resistant Acinetobacter baumannii has been responsible for an increasing number of hospital-acquired infections globally. The study investigated the prevalence of carbapenemase-encoding genes in clinical multidrug-resistant A. baumannii strains. MATERIALS AND METHODS: A total of 100 nonduplicate multidrug-resistant A. baumannii strains were cultured from clinical samples obtained from healthcare facilities in the O. R. Tambo district. The strains were confirmed by detecting the intrinsic bla(OXA-51-like) gene. Antimicrobial susceptibility testing was performed by VITEK(®) 2 and autoSCAN-4 systems. The MIC of imipenem and meropenem was rechecked by E-test. Colistin MIC was confirmed by the broth microdilution method. Real-time PCR was performed to investigate the presence of carbapenemase-encoding genes. RESULTS: Most strains showed high resistance rates (>80%) to the antibiotics tested. Resistance to amikacin, tetracycline, and tigecycline were 50%, 64%, and 48%, respectively. All strains were fully susceptible to colistin. The bla(OXA-51-like) was detected in all strains whilst bla(OXA-23-like), bla(OXA-58-like), bla(OXA-24-like), bla(IMP-1), bla(VIM), and bla(NDM-1) were found in 70%, 8%, 5%, 4%, 3%, and 2% of strains, respectively. None of the tested strains harboured the genes bla(SIM) and bla(AmpC). The coexistence of bla(OXA-23-like), and bla(IMP-1) or bla(OXA-58-like) was detected in 1% and 2% strains, respectively. A distinct feature of our findings was the coharbouring of the genes bla(OXA-23-like), bla(OXA-58-like,) and bla(IMP-1) in 2% strains, and this is the first report in the Eastern Cape Province, South Africa. The intI1 was carried in 80% of tested strains whilst ISAba1/bla(OXA-51-like) and ISAba1/bla(OXA-23-like) were detected in 15% and 40% of the strains, respectively. The detection of bla(OXA-23-like), ISAba1/bla(OXA-51-like), ISAba1/bla(OXA-23-like), and bla(OXA-23-like), bla(OXA-58-like), and bla(IMP-1) carbapenemases in strains had a significant effect on both imipenem and meropenem MICs. CONCLUSIONS: Results showed a high level of oxacillinases producing A. baumannii circulating in our study setting, highlighting the need for local molecular surveillance to inform appropriate management and prevention strategies.